Las figuras de la mujer en el Río de la Plata através de la poética del tango = The figures of women in the Río de la Plata through the poetics of tango - Gadea, Carlos; Bünsow, Theresa (Civitas - Revista de Ciências Sociais, 2017)
When tango arises as cultural expression it is witness and protagonist of the modernization process in Río de la Plata. Its poetry narrates the adventures and misadventures of its protagonists, as they are part of the great social and economic transformations such as industrialization and the growing urbanization. Tango tells about the changes on the cultural values of the passage from the 19th to the 20th century. Among its protagonists, woman has got a central role in the tango’s poetry. The main aim of this text is to analyse the different representations about her. The figure of woman in the tango’s poetry enables us to comprehend this emerging modernity in the Rio de la Plata´s context, as well as her role in narrating the world she lives